Additional records of osmiine bees (Hymenoptera: Megachilidae: Osmiini) from Siberia - Proshchalykin, Maxim Yu.; Müller, Andreas (Zootaxa, 2019)
In addition to a previously published study about Siberian osmiine bees, we here further report records of 19 rarely collected and little known species. Twenty-seven species of osmiine bees are currently known from Siberia. Hoplitis beijingensis Wu, 1987, H. kaszabi Tkalců, 2000, and H. inconspicua Tkalců, 1995 are recorded for the first time for Russia and Hoplitis maritima (Romankova, 1985), Osmia inermis (Zetterstedt, 1838), and O. disjuncta Tkalců, 1995 are new to Siberia. Two species, Hoplitis fulva (Eversmann, 1852) and H. papaveris (Latreille, 1799), are excluded from the list of Siberian bees. The male of Hoplitis daurica (Radoszkowski, 1887) is described for the first time, the taxonomic status of Osmia ephippiata Smith, 1879 is discussed and a lectotype is designated for Hoplitis scita (Eversmann, 1852).